Uterine remodelling during pregnancy and pseudopregnancy in the brushtail possum (Trichosurus vulpecula; Phalangeridae) - Laird, Melanie K. (J Anat, 2017)
The formation of a placenta is critical for successful mammalian pregnancy and requires remodelling of the uterine epithelium. In eutherian mammals, remodelling involves specific morphological changes that often correlate with the mode of embryonic attachment. Given the differences between marsupial and eutherian placentae, formation of a marsupial placenta may involve patterns of uterine remodelling that are different from those in eutherians. Here we present a detailed morphological study of the uterus of the brushtail possum (Trichosurus vulpecula; Phalangeridae) throughout pregnancy, using both scanning and transmission electron microscopy, to identify whether uterine changes in marsupials correlate with mode of embryonic attachment as they do in eutherian mammals. The uterine remodelling of T. vulpecula is similar to that of eutherian mammals with the same mode of embryonic attachment (non‐invasive, epitheliochorial placentation). The morphological similarities include development of large apical projections, and a decrease in the diffusion distance for haemotrophes around the period of embryonic attachment. Importantly, remodelling of the uterus in T. vulpecula during pregnancy differs from that of a marsupial species with non‐invasive attachment (Macropus eugenii; Macropodidae) but is similar to that of a marsupial with invasive attachment (Monodelphis domestica; Didelphidae). We conclude that modes of embryonic attachment may not be typified by a particular suite of uterine changes in marsupials, as is the case for eutherian mammals, and that uterine remodelling may instead reflect phylogenetic relationships between marsupial lineages.